Контроль процесса сварки трением с перемешиванием алюминиевых и магниевых сплавов - Дехелеан, Д.; Койокару, Р.; Раду, Б.; Сафта, В. (Автоматическая сварка, 2008)
A three-dimensional modeling of material flow during the friction stir welding process is presented. The model considers both the heat developed when friction takes place between the material and the tool and the plastic deformation developed by its. The dependency between the real thermal field during the welding process appreciated by infrared thermographic control and the quality of welded joints is analyzed. An original on-line monitoring system for FSW using the infrared thermography is described.